Tissue culture and next-generation sequencing: a combined approach for detecting yam (Dioscorea spp.) viruses - Bömer, M.; Rathnayake, A.I.; Visendi, P.; Sewe, S.O.; Sicat, J.P.A.; Silva, G.; Kumar, P. Lava; Seal, S.E. (Elsevier, 2018)
In vitro culture offers many advantages for yam germplasm conservation, propagation and international distribution. However, low virus titres in the generated tissues pose a challenge for reliable virus detection, which makes it difficult to ensure that planting material is virus-free. In this study, we evaluated next-generation sequencing (NGS) for virus detection following yam propagation using a robust tissue culture methodology. We detected and assembled the genomes of novel isolates of already characterised viral species of the genera Badnavirus and Potyvirus, confirming the utility of NGS in diagnosing yam viruses and contributing towards the safe distribution of germplasm.